2018
DOI: 10.4102/sajid.v33i5.141
|View full text |Cite
|
Sign up to set email alerts
|

Colistin-Resistant Acinetobacter baumannii as a cause of Neonatal Ventriculitis

Abstract: Acinetobacter baumannii causes invasive paediatric infections, including bacteraemia and meningitis, but neonatal meningitis and ventriculitis is uncommon. The treatment of multidrug resistant (MDR) Acinetobacter infections often relies on colistin, a polymyxin antibiotic, as a last resort. Increased use of this drug has led to the emergence of colistin resistance. An unusual case of colistin-resistant Acinetobacter baumannii ventriculitis in a premature neonate managed with intraventricular colistin is descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 7 publications
2
8
0
Order By: Relevance
“…In another review, Katragkou et al discussed the treatment of MDR A. baumannii -associated CNS infection by using IVT/IT colistin alone or as an adjunctive to systemic antimicrobials ( 55 ). In our study, neonatal CSF became sterile within an average of 3.72 days (range 2–8 days), which is similar to earlier literature ( 56 , 57 ). Previous adult and pediatric studies have concluded that the use of IT/IVT colistin was found safe and effective ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In another review, Katragkou et al discussed the treatment of MDR A. baumannii -associated CNS infection by using IVT/IT colistin alone or as an adjunctive to systemic antimicrobials ( 55 ). In our study, neonatal CSF became sterile within an average of 3.72 days (range 2–8 days), which is similar to earlier literature ( 56 , 57 ). Previous adult and pediatric studies have concluded that the use of IT/IVT colistin was found safe and effective ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, neonatal CSF became sterile within an average of 3.72 days (range 2–8 days), which is similar to earlier literature ( 56 , 57 ). Previous adult and pediatric studies have concluded that the use of IT/IVT colistin was found safe and effective ( 56 , 57 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The six colistin-resistant isolates that underwent WGS were also negative for the mcr-1 to mcr-10 genes (all the tested isolates in this study were PCR negative for the mcr-1 to mcr-5 genes). Currently, in South Africa, colistin resistance is not attributed to any of the plasmid-borne mcr genes (Perovic and Chetty, 2016;Mahabeer et al, 2018;Snyman et al, 2020;Nogbou et al, 2022). It is nevertheless still important to monitor and test for the mcr genes in A. baumannii isolates as they can easily be transferred between bacterial species (Gogry et al, 2021).…”
Section: Resistancenodulation-division Adeabc and Adefghmentioning
confidence: 99%